Nutritional status and bioelectrical phase angle assessment in adult Crohn disease patients receiving anti-TNFα therapy. Issue 5 (May 2017) - Emerenziani, Sara; Biancone, Livia; Guarino, Michele Pier Luca; Balestrieri, Paola; Stasi, Elisa; Ribolsi, Mentore; Rescio, Maria Paola; Altomare, Annamaria; Cocca, Silvia; Pallone, Francesco; Cicala, Michele
Abstract: Background: Altered body composition is frequently observed in Crohn's disease (CD) patients. Aims: To investigate the nutritional status, and the effect of different therapeutic regimes in adult CD patients. Methods: Fat free mass (FFM) and BIA-derived phase angle (PhA) were assessed in 45 CD patients, 22 on conventional therapy (CT) and 23 on maintenance therapy with infliximab (MT). Nutritional status was also assessed in 12 CD patients before and following the induction protocol with infliximab. BIA data of CD patients were compared with those of 20 healthy asymptomatic volunteers. In CD patients C Reactive Protein (CRP) and albuminaemia dosage were obtained. Results: The mean values of PhA and of FFM were significantly lower in CT patients when compared with control group and MT patients. Following infliximab treatment FFM increased, although not significantly, while mean phase angle value significantly increased from 4.6 ± 0.3 to 6.2 ± 0.4 (p < 0.05). CRP was significantly lower in MT patients compared to that in CT patients. Conclusion: CD patients on conventional therapy showed a lower FFM and a lower mean phase angle score compared to those on infliximab therapy. Following infliximab treatment the mean phase angle score normalized. PhA is a reliable nutritional indicator in IBD patients and could be considered as an additional tool for assessing response to treatment.